Survey of microbiological and chemical quality of the swimming beaches along the Persian Gulf in Bushehr port (Iranian South Medical Journal, 2015)
Background: Swimming is highly recommended because of its potentially beneficial effects on the joints and people’s general sense of well-being. But unfortunately the discharing of urban and industrial wastewaters into sea with their high level of pathogens, heavy metals and other pollutants, increase concerns about its consequences on swimmers’ health and ecology. The aim of this study was to investigate the microbial and chemical quality of Persian Gulf Sea beaches in Bushehr port and compare it to the existing standards. Materials and Methods: In this study, 30 samples were taken from the beaches at TV-Park, Daneshjo-Park and Eskele-Jofreh, in August 2012. The mean values of total coliforms, fecal coliforms, pseudomonas, HPC, heavy metals and BOD were determined by standard methods. Results: The mean values of total coliforms, fecal coliforms, and pseudomonas along Bushehr port beaches were 540, 165.56 and 6 MPN/100ml respectively.The mean value of HPC was 1580.66 CFU/ml. Also the mean concentrations of Fe, Zn, Pb, Cd, Cr, Cu and BOD were 0.1676, 0.013, 0.025, 0.0016, 0.039, 0 and 21.3 mg/l respectively. Conclusion: The results showed that the mean values of indicator microorganisms in all stations were higher than the existing standards and the mean concentration of heavy metals were lower than the existing standard, which indicates higher pollution more due to urban wastewater compare to industrial wastewater. Therefore Bushehr port beaches are contaminated considering indicator bacteria measurments that can be dangerous for swimmers health.